Aprendizaje invertido como estrategia para contrarrestar la atención dispersa de los niños y niñas del segundo año de educación básica de la Unidad Educativa Iberoamericano cantón Quevedo Provincia de Los Ríos, 2022 - Arévalo Anchundia, Paola Mercedes (2022)
The present thesis has focused mainly on children with attention deficit and how to manage to know how to carry out different learning processes, since not all children learn in the same way, either due to illness, disability or simply due to lack of interest. For this reason, inverted learning has been the main subject of study, its viability, effectiveness and effects on minors, this is where the main objective arises, where it was investigated to reach various sources of information and be able to carry out an arduous study. The importance falls on the need to adapt to the new era, the era of technology, and minors are the ones who are mostly involved in it, in one way or another, although some are in favor and others are against, the Time will continue to advance hand in hand with technology. The methodology applied was of a mixed approach, with methods and techniques of both modalities (qualitative-quantitative) carrying out analyzes and interpretations of texts as well as obtaining results through surveys represented statistically by means of graphs. In conclusion, it should be emphasized that there are more points in favor of applying this tool than not, for the moment the main drawback is the lack of electronic devices that facilitate communication with the teacher, and in the worst case, lack of from Internet.